Integrated coagulation-trickling filter–ultrafiltration processes for domestic wastewater treatment and reclamation - Zhao, Qing-Liang. (2013)
More and more research effort has been put into the development of affordable and high-efficiency wastewater reclamation technology for small communities. In this study, an integrated chemically enhanced primary treatment (CEPT), trickling filter (TF) and ultrafiltration (UF) process was developed with success. Coagulant produced from fly ash was used to enhance primary treatment, while trickling filter packed with coal cinder through four-layer structure without aeration was employed for further removal of COD and ammonium-nitrogen from the CEPT effluent. 95 and 88% removal of COD and ammonium were achieved, while total phosphorus (TP) and suspended solid (SS) were found to be removed completely at a coagulant dosage of 2.5 mL/L in the CEPT–TF–UF system. The product water can meet the standard of Reuse of Recycling Water for Urban Water Quality Standard for Urban Miscellaneous Water Consumption (GB/T 18920-2002, China).